Emerging innovations in neonatal monitoring: a comprehensive review of progress and potential for non-contact technologies - Krbec, Brooke A.; Zhang, Xiang; Chityat, Inbar; Brady-Mine, Alexandria; Linton, Evan; Copeland, Daniel; Anthony, Brian W.; Edelman, Elazer R.; Davis, Jonathan M. (Frontiers in Pediatrics, 2024)
Continuous monitoring of high-risk neonates is essential for the timely management of medical conditions. However, the current reliance on wearable or contact sensor technologies for vital sign monitoring often leads to complications including discomfort, skin damage, and infections which can impede medical management, nursing care, and parental bonding. Moreover, the dependence on multiple devices is problematic since they are not interconnected or time-synchronized, use a variety of different wires and probes/sensors, and are designed based on adult specifications. Therefore, there is an urgent unmet need to enable development of wireless, non-or minimal-contact, and nonadhesive technologies capable of integrating multiple signals into a single platform, specifically designed for neonates. This paper summarizes the limitations of existing wearable devices for neonates, discusses advancements in non-contact sensor technologies, and proposes directions for future research and development.